Teknik Propaganda pada Pemberitaan Calon Walikota Padang Jelang Pemilukada 2018 di Harian Padang Ekspress - Sulthan Jiyad Muqsith; Alkendra Alkhendra; Sheiful Yazan; Arina Fransiska (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2019)
Research is motivated by the development of increasingly mass media. These developments shifted the aim of the media to convey information, educate, entertain and social control. The mass media is also used to launch propaganda with certain techniques in influencing the attitudes and behavior of a particular person or group - in this case the candidate for mayor of Padang. The use of mass media for propaganda occurred in the Padang Ekspress Daily. Qualitative research methods with content Analysis models, focus on physical units, syntactic units, referential units, propositional units and thematic propaganda units techniques on the preaching of candidates for mayor of Padang ahead of the 2018 post-conflict local election in Padang Ekspress daily. The research was conducted in June 2018, the sampling technique was simple random sampling. The researcher found the propaganda techniques used were glittering generalities, bandwidth, transfers, testimonials and card stacking. Preaching pair number 1 uses four propaganda techniques; glittering generalities, tranfers, testimonials, and card stacking. The Mahyeldi-Desri pair uses the five propaganda techniques. Glittering generalities are the most commonly used techniques, card stacking and testimonials are the least used. All analysis units can measure the use of propagation techniques. The various units of physical reporting. The syntactic unit looking at "Mahyeldi", "Emzalmi", "Desri" and "Qur'an" is the most frequently occurring word. Referential units, propositional units and thematic units of news predominantly present equivalent words, propositions and themes about Islam and / or religiosity